From general transfer to deep learning as argument for practical aesthetic school subjects? - Jorunn Spord Borgen; Finn R. Hjardemaal (Taylor & Francis Group, 2017)
This article investigates the empirical ground for transfer thinking about the practical aesthetic school subjects (PAS). We investigate the conceptual framework and methodological possibilities and constraints concerning transfer from the PAS to other domains, and analyse the transfer arguments in arts and crafts and physical education (PE) within the context of the Nordic countries specifically. We find that there is not much research about how educational objectives, content, and teaching and working methods, assessment forms, learning processes and learning outcomes are linked together. Accordingly, the transfer from one school subject to other subjects or domains is challenging to justify. We outline an alternative perspective on transfer in PAS in general, and in arts and crafts and PE specifically that could be investigated more carefully to further the development of a more robust knowledge field.